Електроннi та магнiтнi характеристики поверхнi шпiнелi Co3O4 (111) в наближеннi GGA+U - Kupchak, I.; Serpak, N. (Publishing house "Academperiodika", 2018)
The atomic structure and electronic properties of the spinel Co3O4 (111) surface are calculated within the methods of density functional theory. Possible types of the surface are analyzed, and their formation energies are calculated. Electron states formed at the surface by broken bonds are studied in detail, and their partial density of states is calculated. It is shown that, unlike the bulk of spinel, its surface has nontrivial magnetic properties, because Co atoms acquire an additional magnetic moment under near-surface conditions.